Association of environmental noise exposure with cortisol levels in children from eight European birth cohorts - Arregi, Ane; Robinson, Oliver; Aasvang, Gunn Marit; Andrusaityte, Sandra; Dedele, Audrius; Evandt, Jorunn; Garcia-Baquero, Gonzalo; Krog, Norun Hjertager; Guxens, Mònica; Jaddoe, Vincent W.V.; Karachaliou, Marianna; Lertxundi, Aitana; et al. (Environmental research, 2025)
Environmental noise is a major environmental risk factor for public health. According to the noise reaction model the release of stress hormones like cortisol in response to noise exposure, plays a key role in the development of noise-induced health effects. We aimed to study the association between environmental noise with both acute (UCC) and cumulative (HCC) cortisol levels in children 5–12 years of age. To do so, we analysed data from the HELIX cohort –with spot UCC data- and from the Generation R and INMA cohorts (Gipuzkoa and Sabadell) –with HCC data. The analytical sample involved: 750 HELIX children (mean age = 7.75), 1326 Generation R children (mean age = 6.06), 111 INMA-Sabadell children (mean age = 8.75) and 288 INMA-Gipuzkoa children (mean age = 7.85). Day-evening-night equivalent (Lden) environmental noise exposure during the year of the follow-up was estimated in the addresses of participants, using existing noise maps. Directed acyclic graphs (DAGs) were used to identify appropriate covariates and reduce the chance for biased estimation. We used mixed-effects modelling and linear modelling to examine the association between Lden and cortisol concentration using complete case analyses. None of the models reached the statistical significance. We observed no correlation between HCC and UCC in INMA-Sabadell participants, for whom both urinary and hair cortisol data were available. Future research should prioritize investigating the effects of environmental noise on HCC, as it may serve as a more reliable indicator for assessing associations with chronic exposures. Additionally, future studies on noise-induced health effects in children should incorporate other biomarkers of stress and chronic inflammation to provide a more comprehensive understanding of these associations. •The study focused in the association between environmental noise exposure and urine and hair cortisol levels in children.•We did not observe any statistically significant association between environmental noise exposure and HCC.•Similarly, no significant association was found between environmental noise exposure and UCC.•Future research should incorporate additional biomarkers to further investigate the health effects of noise exposure.